Zero Action on Perfect Crystals for Uq(G₂⁽¹⁾) - Misra, K.C.; Mohamad, M.; Okado, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
The actions of 0-Kashiwara operators on the Uq'(GG₂⁽¹⁾)-crystal Bl in [Yamane S., J. Algebra 210 (1998), 440-486] are made explicit by using a similarity technique from that of a Uq'(D₄⁽³⁾)-crystal. It is shown that Bll ≥ 1 forms a coherent family of perfect crystals.